2017
DOI: 10.3390/ma10020176
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphosis in the Porosity of Recycled Concretes Through the Use of a Recycled Polyethylene Terephthalate (PET) Additive. Correlations between the Porous Network and Concrete Properties

Abstract: In the field of construction, sustainable building materials are currently undergoing a process of technological development. This study aims to contribute to understanding the behavior of the fundamental properties of concretes prepared with recycled coarse aggregates that incorporate a polyethylene terephthalate (PET)-based additive in their matrix (produced by synthesis and glycolysis of recycled PET bottles) in an attempt to reduce their high porosity. Techniques to measure the gas adsorption, water porosi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…The consumption of CH, due to the carbonation progression, and the formation of C-S-H, C-S-A-H, and C-A-H phases gave rise to a refinement of the pore structure, which was studied by mercury intrusion porosimetry (MIP). This technique has been applied in cement-based materials [59]. The addition of MK (S20MK) to the plain lime mortars (S0MK) reduced the mean pore size diameter from 0.83 µm to 0.56 µm in samples tested at 91 curing days (depicted as an example) (Figure 10a).…”
Section: Resultsmentioning
confidence: 99%
“…The consumption of CH, due to the carbonation progression, and the formation of C-S-H, C-S-A-H, and C-A-H phases gave rise to a refinement of the pore structure, which was studied by mercury intrusion porosimetry (MIP). This technique has been applied in cement-based materials [59]. The addition of MK (S20MK) to the plain lime mortars (S0MK) reduced the mean pore size diameter from 0.83 µm to 0.56 µm in samples tested at 91 curing days (depicted as an example) (Figure 10a).…”
Section: Resultsmentioning
confidence: 99%
“…All these results are explained by the reduction in the porosity that SCMs provide to the RAC matrix. For example, Mendivil-Escalante et al (46) studied the micro-porosity of polyethylene-terephthalateadmixed RAC by several methods, and report a strong reduction in total porosity that may improve the performance against ESA.…”
Section: Introductionmentioning
confidence: 99%
“…recycled materials like ceramic and PET reduce the porosity of mortar, for example [58,59]. Research has shown that the addition of both industrial by-products and recycled aggregates can reduce a building's carbon footprint [37,49,60].…”
Section: Building Materialsmentioning
confidence: 99%